Avaliação da proposta da aprendizagem cooperativa como estratégia teórico-metodológica para melhorar o ensino-aprendizagem: estudo de caso em uma escola estadual de educação profissional do Ceará - Leão, Dóris Sandra Silva (2019)
This research aims to evaluate how the theoretical-methodological strategies of cooperative learning are structured to contribute to the improvement of the learning of students of the second grade of high school in a state school of professional education of Ceará. Therefore, it was necessary to understand how the theoretical-methodological strategies of the proposal are structured in the classroom, to enable the constitution of the crucial elements to the consolidation of cooperative principles such as: positive interdependence, promoter interaction, individual responsibility, social skills and group processing. In the theoretical foundation, initially it was tried to delineate the evaluation of the school learning in its broader context, in order to place it in the historical ambit of the Brazilian education, and, with that, to understand it as a ideological practice of the traditional pedagogy. Then, we sought to base the possibility of advancing the evaluation processes, through knowledge about the constructivist conception of learning, shedding light to the formative assessment, with the regulatory function of learning. Following are presented the theoretical and methodological foundations of cooperative learning and the Program for Encouraging Cooperation in School (PRECE), which underlie the cooperative experience in the investigated school. As for the methodology, it is a case study, since it investigates a single group, where the phenomenon happens, driven by the social interaction between the subjects; as for the research approach, it is essentially qualitative, since it aims to bring theory closer to its pedagogical practice, in the light of the contextual factors that determine it; but also with quantitative characteristics, considering the need to collect measurable data for research. Regarding the technical procedures for data collection, a documental analysis was performed, in which the school management documents and the theoretical-methodological instruments of cooperative learning were verified, since they organize and subsidize the pedagogical work of the school; assessments of diagnostic, formative and summative features were used to survey the evolution of students' learning throughout the school year; closed questionnaires were also applied for the initial survey of the profile of teachers and students, as well as for the screening of the qualitative sample; in addition, semi-structured interviews were conducted with teachers and students, with a view to understanding their beliefs and values, revealing the circumstances of behavior from the perspective of cooperative learning; and, finally, participant observation was made in the interviewed teachers' classroom in the interviews, to learn how the phenomenon occurs effectively in the conditions of daily practice. Regarding the strategy for data analysis, we used content analysis, supported by the WebQDA program, which organized the textual collection from categories and record units. It was found, at the end of the research, that the implementation of the cooperative learning proposal based on student protagonism and mediated by situations of mobilizing social interactions, enables a better development of learning, as it promotes intense positive interdependence and mutual help between the students in the learning process, causing the building of intellectual autonomy and, thus, the construction of cognitive and socio-emotional skills.